2016
DOI: 10.1002/ceat.201500324
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Separation of Metal Ions from Aqueous Solutions by Solvent‐Impregnated Resins

Abstract: The recovery and separation of metals from aqueous solutions is one of the research hotspots in hydrometallurgy, environment protection, analytical chemistry, etc. Much attention has been paid to solvent-impregnated resins (SIRs) since these were firstly proposed for the extraction of metals. SIRs are characterized by high efficiency and selectivity, convenient preparation, and easy operation because they combine the unique advantages of solvent extraction and ion exchange. The preparation and features of SIRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 163 publications
(171 reference statements)
0
26
0
1
Order By: Relevance
“…The Langmuir isotherm is commonly used to describe the monolayer adsorption on the homogeneous sites of sorbent . The good fitting of the sorption to the Freundlich isotherm suggests that the sorption of salt ions on the two electrodes is not restricted to one specific class of sites and the adsorption of ions occurs on a heterogeneous surface by monolayer sorption .…”
Section: Resultsmentioning
confidence: 99%
“…The Langmuir isotherm is commonly used to describe the monolayer adsorption on the homogeneous sites of sorbent . The good fitting of the sorption to the Freundlich isotherm suggests that the sorption of salt ions on the two electrodes is not restricted to one specific class of sites and the adsorption of ions occurs on a heterogeneous surface by monolayer sorption .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the Langmuir and Freundlich isotherm models are widely used to depict the adsorption of metal ions onto SIRs [11,24,25]. Langmuir model is commonly used to describe the uptake of metal ions that occurs on a homogeneous surface by monolayer adsorption without any interaction between the adsorbed ions, and the Freundlich model assumes that the adsorption of metal ions occurs on a heterogeneous surface by monolayer adsorption.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Solvent-impregnated resins (SIRs) that were prepared by incorporating extractants onto polymeric matrix have been widely applied in the fields of separation and purification for metals [1][2][3] and organics [4,5] from aqueous solutions, due to their high selectivity, operational simplicity, and environmental friendliness [6,7], which can be traced back to the pioneering work that was conducted by Warshawsky [8], Grinstead [9], and Kroebel and Meyer [10] in the early 1970s. Thus, the preparation and application of the SIRs in analytical and environmental chemistry, hydrometallurgy, and radiochemistry fields are still intensive research topics [11]. However, there are some problems that are embedded in SIRs, such as time-consuming of the impregnation process for the extractants impregnating onto the macroporous matrix, long time of the adsorption equilibrium and low adsorption capacity of the SIRs for metal ions, which may impede the industrial application of SIRs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pine bark is one of the most abundant agro‐industrial wastes which has been mostly used as fuel. In a previous study , it was found that after chemical modification pine bark could be an interesting biosorbent for uptaking Cr(III) when compared not only with similar biosorbents but also with ion‐exchange resin , .…”
Section: Introductionmentioning
confidence: 99%